Glycosylation-independent binding of monoclonal antibody toripalimab to FG loop of PD-1 for tumor immune checkpoint therapy. Issue 4 (19th May 2019) - Liu, Hongchuan; Guo, Lijing; Zhang, Jing; Zhou, Yuehua; Zhou, Jinwei; Yao, Jian; Wu, Hai; Yao, Sheng; Chen, Bo; Chai, Yan; Qi, Jianxun; Gao, George F.; et al.
ABSTRACT: Monoclonal antibody (mAb)-based blockade of programmed cell death 1 (PD-1) or its ligand to enable antitumor T-cell immunity has been successful in treating multiple tumors. However, the structural basis of the binding mechanisms of the mAbs and PD-1 and the effects of glycosylation of PD-1 on mAb interaction are not well understood. Here, we report the complex structure of PD-1 with toripalimab, a mAb that is approved by China National Medical Products Administration as a second-line treatment for melanoma and is under multiple Phase 1-Phase 3 clinical trials in both China and the US. Our analysis reveals that toripalimab mainly binds to the FG loop of PD-1 with an unconventionally long complementarity-determining region 3 loop of the heavy chain, which is distinct from the known binding epitopes of anti-PD-1 mAbs with structural evidences. The glycan modifications of PD-1 could be observed in three potential N-linked glycosylation sites, while no substantial influences were detected to the binding of toripalimab. These findings benefit our understanding of the binding mechanisms of toripalimab to PD-1 and shed light for future development of biologics targeting PD-1. Atomic coordinates have been deposited in the Protein Data Bank under accession code 6JBT.